Evaluating Protein Tyrosine Phosphatase 1B Inhibitory Activity of Bioactive Compounds from Momordica charantia for Diabetes Treatment Type 2 by using Molecular Docking Method - Hong Nhung, Nguyen; Thi Thu Hang, Ta; Khanh Linh, Vu; Bao Kim, Nguyen; The Hai, Pham; Hong Minh, Phan; Thanh Tung, Bui (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 2, 2021)
Diabetes mellitus is a chronic metabolic disease, which is characterized by elevated blood glucose levels, caused by a deficiency in insulin secretion from the β pancreatic’s cells or the operability of insulin. The protein tyrosine phosphatase 1B (PTP1B) catalyzes to removing the phosphate group from the insulin receptor's phosphotyrosine, then reducing insulin’s effects. Therefore, inhibiting this enzyme is an effective method to treat diabetes mellitus. Momordica charantia is effective in the treatment of diabetes mellitus. In this study, we evaluated the inhibitory effects of PTP1B enzyme of Momordica charantia ’s compounds by using molecular docking method. Based on the previous publication of Momordica charantia , we have collected 57 compounds. The results showed that 3 compounds have PTP1B inhibitory effect stronger than the positive control including Luteolin-7- O -glycoside, apigenin-7- O -glycoside and δ-cadinene. Analysis Lipinski Rule of Five showed that Luteolin-7- O -glycoside and δ-cadinene have drug-likeness properties. Moreover, predict ADMET showed that these two compounds have good intestinal absorption, not metabolized in the liver, excretion by the kidney and low toxicity. Conclusion: Our findings suggested that luteolin-7- O -glycoside, δ-cadinene may be potential natural product compounds for diabetes treatment type 2. Keywords Momordica charantia, PTP1B, Diabetes mellitus, Molecular docking, in silico. References [1] World Health Organization, Diabetes, https://www.who.int/health-topics/diabetes (accessed on: March 10th, 2021). [2] International Diabetes Federation, IDF Diabetes Atlas 9th Edition, Diabetes is Rising Worldwide... and is Set to Rise Even Further, https://diabetesatlas.org/en/sections/worldwide-toll-of-diabetes.html, (accessed on: March 10th, 2021). [3] N. B. Ngoc, Z. L. Lin, W. Ahmed, Diabetes: What Challenges Lie Ahead for Vietnam?, Annals of Global Health, Vol. 86, No. 1, 2020, p. 1, http://doi.org/10.5334/aogh.2526. [4] H. Cho, Protein Tyrosine Phosphatase 1B (PTP1B) and Obesity, Vitamins & Hormones, Vol. 91, 2013, pp. 405-424, https://doi.org/10.1016/B978-0-12-407766-9.00017-1. [5] J. M. Zabolotny, Y. B. Kim, L. A. Welsh, E. E. Kershaw, B.G. Neel, B. B. Kahn, Protein-Tyrosine Phosphatase 1B Expression is Induced by Inflammation in vivo, Journal of Biological Chemistry, Vol. 283, No. 21, 2008, pp. 14230-14241, https://doi.org/10.1074/jbc.M800061200. [6] J. Montalibet, B. P. Kennedy, Therapeutic Strategies for Targeting PTP1B in Diabetes, Drug Discovery Today: Therapeutic Strategies, Vol. 2, No. 2, 2005, pp. 129-135, https://doi.org/10.1016/j.ddstr.2005.05.002. [7] S. Jia, M. Shen, F. Zhang, J. Xie, Recent Advances in Momordica charantia: Functional Components and Biological Activities, International Journal of Molecular Sciences, Vol. 18, No. 12, 2017, pp. 2555, https://doi.org/10.3390/ijms18122555. [8] P. Kulkarni, S. Lohidasan, K. Mahadik, Isolation, Characterisation and Investigation of in vitro Antidiabetic and Antioxidant Activity of Phytoconstituents from Fruit of Momordica charantia Linn, Natural Product Research, Vol. 35, No. 6, 2019, pp. 1035-1037, https://doi.org/10.1080/14786419.2019.1613400. [9] Z. Liu, J. Gong, W. Huang, F. Lu, H. Dong, The Effect of Momordica charantia in the Treatment of Diabetes Mellitus: A Review, Evidence-Based Complementary and Alternative Medicine, Vol. 2021, 2021, pp. 1-14, https://doi.org/10.1155/2021/3796265. [10] X. Y. Meng, H. X. Zhang, M. Mezei, M. Cui, Molecular Docking: A Powerful Approach for Structure-Based Drug Discovery, Current Computer-Aided Drug Design, Vol. 7, No. 2, 2011, pp. 146-157, https://doi.org/10.2174/157340911795677602. [11] B. K. Shoichet, S. L. McGovern, B. Wei, J. J. Irwin, Lead Discovery Using Molecular Docking, Current Opinion in Chemical Biology, Vol. 6, No. 4, 2002, pp. 439-446, https://doi.org/10.1016/S1367-5931(02)00339-3. [12] C. A. Lipinski, Lead-and Drug-like Compounds: the Rule-of-five Revolution, Drug Discovery Today: Technologies, Vol. 1, No. 4, 2004, pp. 337-341, https://doi.org/10.1016/j.ddtec.2004.11.007. [13] B. Jayaram, T. Singh, G. Mukherjee, A. Mathur, S. Shekhar, V. Shekhar, Sanjeevini: A Freely Accessible Web-server for Target Directed Lead Molecule Discovery, Eleventh International Conference on Bioinformatics (InCoB2012): Bioinformatics, Vol. 13, 2012. pp. 1-13, https://doi.org/10.1186/1471-2105-13-s17-s7. [14] D. E. Pires, T. L. Blundell, D. B. Ascher. pkCSM: Predicting Small-Molecule Pharmacokinetic and Toxicity Properties Using Graph-Based Signatures, Journal of Medicinal Chemistry, Vol. 58, No. 9, 2015, pp. 4066 - 4072, https://doi.org/10.1021/acs.jmedchem.5b00104. [15] A. Braca, T. Siciliano, M. D’Arrigo, M. P. Germanò, Chemical Composition and Antimicrobial Activity of Momordica charantia Seed Essential Oil, Fitoterapia, Vol. 79, No. 2, 2008, pp. 123-125, https://doi.org/10.1016/j.fitote.2007.11.002. [16] S. Sur, R. B. Ray. Bitter Melon (Momordica Charantia), A Nutraceutical Approach for Cancer Prevention and Therapy, Cancers, Vol. 12, No. 8, 2020, pp. 2064, https://doi.org/10.3390/cancers12082064. [17] L. Harinantenaina, M. Tanaka, S. Takaoka, M. Oda, O. Mogami, M. Uchida, Y. Sakawa, Momordica charantia Constituents and Antidiabetic Screening of the Isolated Major Compounds, Chemical and Pharmaceutical Bulletin, Vol. 54, No. 7, 2006, pp. 1017-1021, https://doi.org/10.1248/cpb.54.1017. [18] K. A. Lantz, S. G. E. Hart, S. L. Planey, M. F. Roitman, I. A. R. White, H. R. Wolfe, M. P. McLane, Inhibition of PTP1B by Trodusquemine (MSI‐1436) Causes Fat‐specific Weight Loss in Diet‐induced Obese Mice, Obesity, Vol. 18, No. 8, 2010, pp. 1516-1523, https://doi.org/10.1038/oby.2009.444. [19] R. Horax, N. Hettiarachchy, S. Islam, Total Phenolic Contents and Phenolic Acid Constituents in 4 Varieties of Bitter Melons (Momordica Charantia) and Antioxidant Activities of their Extracts, Journal of Food Science, Vol. 70, No. 4, 2005, pp. C275-C280, https://doi.org/10.1111/j.1365-2621.2005.tb07173.x. [20] S. J. Wu, L. T. Ng, Antioxidant and Free Radical Scavenging Activities of Wild Bitter Melon (Momordica charantia Linn. var. abbreviata Ser.) in Taiwan, LWT-Food Science and Technology, Vol. 41, No. 2, 2008, pp. 323-330, http://dx.doi.org/10.1016%2Fj.lwt.2007.03.003. [21] J. B. Xiao, P. Hogger, Dietary Polyphenols and Type 2 Diabetes: Current Insights and Future Perspectives, Current Medicinal Chemistry, Vol. 22, No. 1, 2015, pp. 23-38, https://doi.org/10. 2174/0929867321666140706130807. [22] Y. Zang, K. Igarashi, Y. Li, Anti-diabetic Effects of Luteolin and Luteolin-7-O-glucoside on KK-Ay Mice; Bioscience, Biotechnology, and Biochemistry, Vol. 80, No. 8, 2016, pp. 1580-1586, https://doi.org/10.1080/09168451.2015.1116928.